Note—On Total Sojourn Time in Networks of Queues - Lemoine, Austin J. (Management Science, 1979)
A note and correction of the author's paper (Lemoine, A. J. 1977. Networks of queues—a survey of equilibrium analysis. Management Sci. 24 (4) 464–481.).